Implementing project based learning in the foreign language learning of the transition students of ASPAEN- colegio el Rosario (2016)
This pedagogical project seeks to determine the impact of implementing PBL in the foreign language learning of the transition students by working through four specific objectives: to diagnose the process with the English in preschool; to implement PBL; to assess the students’ progress under PBL criteria and; to monitor the success of this approach. This process was done by a qualitative paradigm, the research method is implementational studies and the type of research is action research. This work allowed me to determine the interesting and meaningful results of the students and the progress that they had in the use of PBL approach. At the end the English coordinator, teachers, families and students were satisfied with the students’ success.